2015
DOI: 10.1097/aog.0000000000001039
|View full text |Cite
|
Sign up to set email alerts
|

Uncontained Compared With Contained Power Morcellation in Total Laparoscopic Hysterectomy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Nevertheless, application of a bag system consumes time, which was reported to prolong surgery by 20-30 min as compared to retrospective controls with uncontained morcellation [14,19,20]. In the present study, median total time associated with the bag use was only 10 min, confirming the positive experience from our pilot work [16].…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, application of a bag system consumes time, which was reported to prolong surgery by 20-30 min as compared to retrospective controls with uncontained morcellation [14,19,20]. In the present study, median total time associated with the bag use was only 10 min, confirming the positive experience from our pilot work [16].…”
Section: Discussionsupporting
confidence: 79%
“…These techniques have yet to be studied in depth but represent creative and potentially safer methods of tissue specimen extraction using a minimally invasive approach. In-bag power morcellation has been noted to increase operating time by 20 to 26 minutes [24,25]. The purpose of contained morcellation is to avoid dissemination of an occult malignancy, parasitic fibroids, and direct visceral injuries from morcellation.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In their studies, Vargas et al 39 and Winner et al 40 found that contained morcellation during laparoscopic hysterectomy was associated with a 20-minute increase in operative time and with no difference in other perioperative outcomes. The increase of 20 minutes may diminish across time when surgeons become familiar with this new technique.…”
Section: Improved Methods For Morcellationmentioning
confidence: 99%